Micropropagation Technology of Bambusa bambos through Shoot Proliferation - Arya, Sarita; Sharma, Sushma (Indian Forester, 1998)
Bamboos arc versatile multipurpose forest produce which playa vital role in our domestic economy. Bambusa bambos is the principle source for paper and pulp besides being used for constructional purposes and provides food materials. The conventional methods of its propagation have a lot of problems which restrict its multiplication on a large scale. A tissue culture technology is developed for large scale multiplication of Bambusa bambos which is discussed.